Halichondriidae Gray, 1867 from the Northeastern Brazil with description of a new species - Santos, George Garcia; Nascimento, Elielton; Pinheiro, Ulisses (Zootaxa, 2018)
In this paper we report and describe material of Halichondriidae sampled at 11 different stations in the Brazilian northeastern coast. Halichondria (Halichondria) marianae sp. nov. is a massively encrusting sponge, with firm texture, soft, fleshy, but compact and compressible. Color in vivo is dark green, becoming grayish or brown after fixation in ethanol; the spicules are smooth oxeas. Amorphinopsis atlantica from the Northeastern Brazil is thickly encrusting to massively, also with firm texture, color in vivo is usually yellow to dark green and both distributed in different regions, brownish after fixation in ethanol; the spicules are smooth oxeas and styles. A taxonomic study of these samples is given, including description and illustrations.